Contextual teaching and learning handout on food digestive system materials - Asmaul Nadira; Hamka Lodang; Andi Rahmat Saleh (Universitas Negeri Padang, 2023)
Education is the key to improving the condition of society, because the aim is to educate and develop all existing potential. Its implementation involves many parties in order to achieve educational goals properly. This research was conducted to contribute to these educational goals, specifically to develop handouts based on contextual teaching and learning. This development uses the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Researchers develop handouts that have been validated beforehand. This validation process uses several questionnaires by experts. In addition, other instruments have also been designed, in the form of teacher and student response questionnaires. After implementation, the research product was evaluated by analyzing data for validity and practicality. The results of the study show the validity value with an average of 4.22 in the valid category, while the responses of teachers and students are included in the very practical category with an average of 89.12%.